Penerapan Python Dalam Data Mining Untuk Prediksi Kangker Paru - Baiq Andriska Candra Permana; Muhammad Djamaluddin (Infotek: Jurnal Informatika dan Teknologi, 2023)
Lung cancer is one of the groups of cancer that causes the most deaths, including in Indonesia. Many people with lung cancer do not realize that they are infected with lung cancer, which causes delays in treating this disease. For this reason, it is necessary to have a method that has a good level of accuracy in making a prediction so that later with a good level of accuracy it can be a reference for the development of an Artificial Intelligence (AI) in the world of health to detect lung cancer early. The proposed study uses the c4.5 algorithm to predict the likelihood of patients with lung cancer by providing the final result in the form of the prediction accuracy of the proposed algorithm. To carry out data mining implementation using the Python programming language by utilizing the library that has been provided to make it easier to implement machine learning. In this study the use of c4.5 was able to predict with an accuracy rate of 86%. This level of accuracy can be said to be worthy of being used as a reference to be able to predict lung cancer patients based on the symptoms that appear in the patient